Toward a New Aesthetics : Institutional Criticism in Art Education from 1900 to Today - Neugärtner, Sandra, (Doing Arts Thinking: Arts Practice, Research and Education ;, 2026)
Has art education lost its critical edge? Is art becoming just another form of intellectual labor? Toward a New Aesthetics argues that the increasing "scientification" of art is directly linked to a decline in institutional self-critique. This study offers the first comprehensive examination of institutional critique within art schools. Through contributions from leading art historians, critics, educators, and artists, readers will trace a century of critical engagement, from radical challenge and transformative beginnings to today's institutional affirmation. Exploring international case studies, the book reveals how the rise of artistic research has profoundly impacted art's critical potential within the global knowledge economy. Contributors are: Bernard Akoi-Jackson, Katherine Bruhn, Benjamin Buchloh, Emily Ruth Capper, Nicola Foster, Tom Holert, Erika Kindsfather, Sooyoung Leam, Sandra Neugärtner, Isabel Nogueira, Noa Sadka, Jeffrey Saletnik, Christine-Marie Schoel, Rebecca Sprowl and Jack Watts.